2022
DOI: 10.17645/si.v10i2.5105
|View full text |Cite
|
Sign up to set email alerts
|

Educational and Occupational Aspirations: A Longitudinal Study of Vienna Youth

Abstract: During their transition from lower to upper secondary education, young peoplemake educational and occupational choices driven by their aspirations. Such aspirations are shaped by the individuals’ social environment, their idea of what seems achievable and desirable, and their experiences. Therefore, aspirations can change during the transitional phase. In this article, we explore the development of educational and occupational aspirations of young people over three years. At the start of the study period, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Another study found math achievement to be a "critical filter" to subsequent math careers (Shapka et al, 2006). At the individual level, a myriad of factors affect the development of occupational expectations; but school performance, migration background, and parental education play important roles in explaining occupational expectations (Valls et al, 2022). This information allows us to control the effect of individual variables at the first level (both gradual and categorical) so that we can calculate the effect of the country…”
Section: Independent Variablesmentioning
confidence: 99%
“…Another study found math achievement to be a "critical filter" to subsequent math careers (Shapka et al, 2006). At the individual level, a myriad of factors affect the development of occupational expectations; but school performance, migration background, and parental education play important roles in explaining occupational expectations (Valls et al, 2022). This information allows us to control the effect of individual variables at the first level (both gradual and categorical) so that we can calculate the effect of the country…”
Section: Independent Variablesmentioning
confidence: 99%
“…Moreover, the life course perspective emphasises the need for using longitudinal analyses to examine transitions as processes. Therefore, several contributions either deal with facets of stability or change in the transition, such as Mühlböck et al's (2022) work on occupational aspirations, Fischer-Browne's (2022) article on the compromise formation between occupational aspirations and training occupation, or Valls et al's (2022) research on the alignment of occupational and educational aspirations. Furthermore, some articles investigate individual developmental processes in the transition, such as Gellermann and Fuchs' (2022) work on autonomy, Fasching and Felbermayr's (2022) research on cooperation, Wintersteller et al's (2022) study on young people's demands, or insecurity by Thoma and Langer (2022).…”
Section: The Research Perspectives Of the Thematic Issuementioning
confidence: 99%
“…The avoidance of downward mobility in educational decisions is supported by empirical evidence (e.g., Becker, 2003;Holm and Jaeger, 2008;Stocke, 2007). Students from a privileged background are more likely to maintain their higher aspirations over time, thus high and low aspirations tend to get locked-in (Valls et al, 2022).…”
Section: Family Background and Aspirationsmentioning
confidence: 97%